HUBUNGAN KECERDASAN EMOSIONAL DENGAN KOMPETENSI PEDAGOGIK GURU TK SE-KECAMATAN TENAYAN RAYA - Eka Kusuma Wardani; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:The aim of this reserch is to know the corelation of emotional intelligence and pedagogical competence of kindergarten teachers sub-district Tenayan Raya. The population in this study were kindergarten teachers with a Bachelor of Education background (S1) in formal and non-formal institutions totaling 78 teachers, the sample of this study was 58 teachers. Method of this research is Pearson product moment correlation to see relationship between variables of work emotional intelligence and pedagogical competence. The technique of collecting data used tests and quistioner in Likert scale form. The technique of analyzing data used scale test and statistic analitical by using SPSS program for Windows Ver.17. Based of this research there is level of emotional intelligence of teachers is in the high category with empirical values of 71,88 and the level of pedagogical competence is in the moderate category with empirical values of 30,45. Based on the hypothesis test, there is a positive and significant relationship between emotional intelligence and pedagogical competence of kindergarten teachers Tenayan Raya District. This can be seen from the correlation coefficient of rxy = 0.566 and the significance level of 0.000 <0.05. The level of the relationship between emotional intelligence and pedagogical competencies is included in the medium category with the determinant coefficient value of KD = r² x 100% = 32%, meaning that emotional intelligence has an effect of 32% on pedagogic competence.Key Words : Emotional Intelligence , Pedagogic Competence